Rubiothrips Schliephake, a newly recorded genus of Thripinae from China (Thysanoptera: Thripidae) - Majid Mirabbalou (نامه انجمن حشره‌شناسی ایران)
Rubiothrips vitis (Priesner) of the subfamily Thripinae (Thysanoptera: Thripidae) collected from Sichuan Province is reported in this paper, which represents the first record of both the genus and the species from China.